Carotid artery and cerebral blood flow during experimental cardiopulmonary resuscitation: A systematic review of the literature. (May 2019) - Lucchetta, Luca; Kwan, Timothy N.; Kosaka, Junko; Tanaka, Aiko; Eastwood, Glenn M.; Chan, Matthew; Martensson, Johan; May, Clive N.; Bellomo, Rinaldo
Abstract: Background: The carotid artery blood flow (CABF) or cerebral blood flow (CBF) achieved with current techniques of cardiac compression in humans are unknown. Animal experiments may provide useful information on such flows and on possible techniques to optimize them. Objectives: To obtain an estimate of carotid and cerebral blood flows during cardiac compression with different techniques. Methods: We performed a systematic review of all studies in the English literature that measured the CABF and/or CBF during cardiac compression in experimental models of cardiac arrest, expressed as a percentage of baseline (pre-arrest) values. We compared the effect of vasopressor use, thoracic compression technique, pre-arrest infusion and animal model on maximum blood flows using standard statistical methodologies. Results: Overall, 133 studies were reviewed. Of these, 45 studies provided information only on CABF; 77 only on CBF, and 11 studies on both flows. The overall weighted mean (±SD) CABF was 35.2 ± 27.7% of baseline. Porcine studies showed lower CABF when vasopressors were used (p = 0.0002). Studies of CBF reported a weighted mean value of 66.5 ± 48.5% of baseline. Adjunctive vasopressor therapy significantly increased CBF (p = 0.007), as did fluid administration (P = 0.049). In studies reporting both CABF and CBF, the median CABF/CBF ratio was 0.67 (range 0.21–1.96). Conclusions: During experimental cardiac compression, compared to baseline, CABF appears to decrease much more than CBF. However results should be regarded with caution. They are affected by ancillary interventions and measurement methods, variability is marked and, in experiments measuring CABF and CBF simultaneously, their ratios range well outside physiologically plausible values.